Story-Based Exploratory Learning Model to Improve Students' Critical Thinking Skills and Religious Understanding - Ciptadi, M. Teguh; Mochtar, Asmaji; Maksun, Toha (Journal of Islamic Education, 2025)
This research explores the use of the story of Prophet Musa and Khidr in Surah Al-Kahfi as an exploratory learning model to enhance students' critical thinking skills and religious understanding. Employing a qualitative descriptive approach, data were collected through interviews, observations, and documentation involving various stakeholders, including teachers, students, and administrative staff. The validity of the data was ensured through triangulation and member checking, while thematic analysis was utilized to interpret the findings. The study reveals that the integration of the story into the learning process fosters an interactive environment where students engage in critical reflection and discussion. Through guided inquiry and collaborative learning, students develop their analytical skills as they navigate religious concepts in a meaningful context. This process encourages students to draw connections between their faith and personal experiences, thereby enhancing their critical thinking capabilities. The originality of this research lies in its innovative adaptation of a traditional narrative into a modern educational framework, offering insights into the practical application of Qur'anic stories in classrooms. By focusing on the process of learning rather than solely on outcomes, this study contributes to the discourse on value-based education in Islamic settings and demonstrates the potential of story-based learning to cultivate critical thinkers in contemporary education.